2015
DOI: 10.4238/2015.april.17.3
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGFB1 polymorphism in the development of metastatic brain tumors in non-small cell lung cancer patients

Abstract: ABSTRACT. We conducted a case-control study to investigate the role of 3 single-nucleotide polymorphisms of the gene encoding transforming growth factor-b1 (TGFB1) in the development of metastatic brain tumors in non-small cell lung cancer patients. The polymorphisms in TGFB1 rs4803455, rs1800469, and rs1800470 were evaluated by polymerase chain reaction-restriction fragment length polymorphism. Odds ratios and their corresponding 95% confidence intervals were used to assess the influence of TGFB1 rs4803455, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
2
6
0
1
Order By: Relevance
“…These 2 genes were associated with the tumour growth factor (TGF)beta signaling pathway, 32 and it has been reported that the TGF-beta signaling pathway is related to BM. 33 Besides, TP53 and EGFR mutations were observed in both primary and metastatic lesions, which is consistent with a previous study. 31 In the future, more mutations may be found based on new techniques, such as ctDNA detection of cerebrospinal fluid (CSF), which has attracted much attention because it may also display the genetic information of BM and have therapeutic indications.…”
Section: Discussionsupporting
confidence: 92%
“…These 2 genes were associated with the tumour growth factor (TGF)beta signaling pathway, 32 and it has been reported that the TGF-beta signaling pathway is related to BM. 33 Besides, TP53 and EGFR mutations were observed in both primary and metastatic lesions, which is consistent with a previous study. 31 In the future, more mutations may be found based on new techniques, such as ctDNA detection of cerebrospinal fluid (CSF), which has attracted much attention because it may also display the genetic information of BM and have therapeutic indications.…”
Section: Discussionsupporting
confidence: 92%
“…These discrepancies may be reconciled by differences in ethnic origin between our Tunisian population and Asian women. A possible association between the TGF-β1 rs1800469 and the risk of cancers yielded controversial results, in part due to the type of cancer and ethnic background of study participants [50][51][52][53][54][55][56][57]. Functionally, the TGF-β1 promoter variant rs1800469 (-509C/T) was associated with altered TGF-β1 plasma level and emphasized by the almost double level of circulating TGF-β1 in heterozygous (C/T) and homozygous (T/T) as compared to homozygous (C/C) genotype carriers [58].…”
Section: Discussionmentioning
confidence: 99%
“…When −800G/A (A>G) exist, the binding activity of AP1 with this site is increased, which would promote the transcription and translation of the TGF-β1 gene (12). For HIF-1, the presence of either A or G is not relevant and can be combined, however, for G, the competitive binding with AP1 would be formed (13). TGF-β1 gene polymorphism is also associated with self-autoimmune diseases, repair in trauma, inflammatory reaction, organ fibrosis and other diseases (14,15).…”
Section: Discussionmentioning
confidence: 99%